The effects of n-3 fatty acids and Rosa damascena extract on primary dysmenorrhea - Davaneghi, Soheila; Tarighat-Esfanjani, Ali; Safaiyan, Abdolrasool; Fardiazar, Zahra (Progress in Nutrition, 2017)
Background: Primary dysmenorrhea is painful contractions of the lower abdomen without abnormal pelvic pathology. Aims: Because high prevalence of dysmenorrhea and its effects on women’s social activities, the purpose of this study was to investigate the effects of separate and concurrent supplementation of n-3 fatty acid and Rosa damascene extract (RDE) on primary dysmenorrhea complaints. Study design: Double blind clinical trial. Methods: In this study, 120 university students were randomly allocated with equal size into two groups [Fish oil (FO) Factor groups: one with one-gram soft gel capsule of fish oil (60) and other without it (60)], then each group was randomly allocated with equal size into two groups (RDE Factor groups: one with one-gram capsules of RDE (30) and other without it (30)), for 2 months. And all data was measured three times in these four groups, at the beginning of the study 30th day and 60th day. Pain intensity and quantity of bleeding were measured by visual analog scale (VAS), Higham Pictorial blood loss assessment charts methods respectively. Results: After 2 months treatment, pain intensity was decreased significantly in FO (p=0.02), and RDE (p<0.01) groups but remained high among those who received both of FO and RDE (p=0.27). Reduction of bleeding days was significant (p<0.01) with separate supplementation of FO and RDE but concurrent use of them has no significant effect (p=0.75) on bleeding duration. The amount of bleeding does not changed significantly in any groups. Conclusion: Our results suggest, omega-3 fatty acids and RDE separately have analgesic effect on pain severity and can decrease bleeding duration of dysmenorrhea as nutritional supplements only when used separately.